Association of modified dementia risk score with cerebrospinal fluid biomarkers and cognition in adults without dementia - Li, Qiong-Yao; Fu, Yan; Cui, Xin-Jing; Wang, Zuo-Teng; Tan, Lan; , for the Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Aging Neuroscience, 2024)
Introduction This study aimed to investigate the cognitive profile and prospective cognitive changes in non-demented adults with elevated Modified Dementia Risk Scores (MDRS), while also exploring the potential relationship between these associations and cerebrospinal fluid (CSF) biomarkers of Alzheimer’s disease (AD) pathology and neuroinflammation. Methods Within the Chinese Alzheimer’s Biomarker and LifestylE (CABLE) database, 994 participants without dementia were assessed on MDRS, CSF biomarkers and cognition. We examined the associations of the MDRS with CSF biomarkers and cognitive scores using linear regressions. Causal mediation analyses were conducted to analyze the associations among MDRS, brain pathologies, and cognition. The Alzheimer’s Disease Neuroimaging Initiative (ADNI) study was used to validate the mediation effects and to investigate the longitudinal association between MDRS and cognitive decline. Results The results revealed that higher MDRS were linked to poorer cognitive performance (Model 1: PFDR < 0.001; Model 2: PFDR < 0.001) and increases in CSF levels of phosphorylated tau (P-tau, Model 1: PFDR < 0.001; Model 2: PFDR < 0.001), total tau (T-tau, Model 1: PFDR < 0.001; Model 2: PFDR < 0.001), P-tau/Aβ42 ratio (Model 1: PFDR = 0.023; Model 2: PFDR = 0.028), T-tau/Aβ42 ratio (Model 1: PFDR < 0.001; Model 2: PFDR < 0.001) and soluble triggering receptor expressed on myeloid cells 2 (sTrem2, Model 1: PFDR < 0.001; Model 2: PFDR < 0.001) in the CABLE study. The impact of MDRS on cognition was partially mediated by neuroinflammation and tau pathology. These mediation effects were replicated in the ADNI study. Baseline MDRS were significantly associated with future cognitive decline, as indicated by lower scores on the Mini-Mental State Examination (MMSE, Model 1: PFDR = 0.045; Model 2: PFDR < 0.001), ADNI composite memory score (ADNI-MEM, Model 1: PFDR = 0.005; Model 2: PFDR < 0.001), ADNI composite executive function score (ADNI-EF, Model 1: PFDR = 0.045; Model 2: PFDR < 0.001), and higher score on the Alzheimer’s Disease Assessment Scale (ADAS13, Model 1: PFDR = 0.045; Model 2: PFDR < 0.001). Discussion The findings of this study revealed significant associations between MDRS and cognitive decline, suggesting a potential role of tau pathology and neuroinflammation in the link between MDRS and poorer cognitive performance in individuals without dementia. Consequently, the MDRS holds promise as a tool for targeted preventive interventions in individuals at high risk of cognitive impairment.